Risk and Resilience Among Mothers and Fathers of Primary School Age Children With ASD in Malaysia: A Qualitative Constructive Grounded Theory Approach - Ilias, Kartini; Cornish, Kim; Park, Miriam Sang-Ah; Toran, Hasnah; Golden, Karen Jennifer (Frontiers in Psychology, 2019)
Little is known about the coping and resilience experiences of parents of children with autism spectrum disorder (ASD) in the Malaysian cultural context. This study utilized a qualitative methodological approach adopting constructive grounded theory. The study sought to address the lack of research to date exploring the risk and protective experiences that contribute to parental stress and resilience for parents of primary school age children with ASD in the Malaysian setting. Twenty-two parents of children with ASD (13 mothers and 9 fathers) participated in semi-structured interviews. A strength of the study was the inclusion of both mother and father participant perspectives. The interviews lasted 50–80 minutes (mean = 67.5 minutes). The 22 parents had a total of 16 children (12 males; 4 females) formally diagnosed with ASD. Child age ranged between 5–12 years (mean age: 8.44). Overall, analysis of the 22 interviews revealed four prominent themes – “initial reaction to child’s ASD symptoms and diagnosis”, “family life affected by a child with ASD”, “awareness about ASD in Malaysia”, and “coping strategies, wellbeing, and becoming resilient”. The first three themes revolved around stress and adversity, and, the adaptability and acceptance of the parents. These processes illustrated the risks experienced by the parents of children with ASD in Malaysia. The last theme especially highlighted the strengths and determination of the parents and illustrated the protective experiences and processes that helped parents to develop and enhance resilience. Overall, the findings revealed that resilience develops synergistically and dynamically from both risk and protective experiences across different levels–individual, family, community, society and government. The findings motivated the development of our theoretical model of resilience that can help health professionals tailor assessment and interventions for parents of children with ASD in the Malaysian context. Clinical, policy, and research suggestions were discussed.